Evaluating End-User Satisfaction of Retail Minimarket Applications Using the Net Promoter Score Method - S, M Fakhri (PT. Lentera Ilmu Publisher, 2026)
The rapid adoption of digital applications in retail minimarkets has made end-user satisfaction a critical factor influencing customer loyalty and continued usage. This study evaluates end-user satisfaction of a retail minimarket application using the Net Promoter Score (NPS) method, which measures users’ willingness to recommend the application to others. A quantitative approach was employed by distributing an NPS-based questionnaire to active users of the application. Respondents were classified into promoters, passives, and detractors based on their ratings. The results show that 52.0% of users were promoters, 27.3% were passives, and 20.7% were detractors, resulting in an NPS value of 31.3. This positive score indicates that the application is generally well received and demonstrates a satisfactory level of user loyalty. However, feedback from passive and detractor users reveals opportunities for improvement in system performance and feature completeness. Overall, the study confirms that the NPS method is an effective and practical tool for assessing end-user satisfaction in retail minimarket applications.